Microorganisms and their Role in Yogurt Preparation - Azimova Sanobar,; Tuychiyeva Dilfuza Sidikjanovna, (American Journal of Biology and Natural Sciences, 2025)
This article examines the role of microorganisms in yogurt production, covering historical aspects of its origin, chemical composition, and impact on human health. The key technological stages of yogurt production are described, including pasteurization, homogenization, and fermentation, in which Lactobacillus bulgaricus and Streptococcus thermophilus play a crucial role. A comparative analysis of the chemical composition of different types of yogurts is presented, detailing protein, fat, carbohydrate, vitamin, and mineral content. Both the positive effects associated with probiotic properties and the potential risks of bacterial contamination are considered. The relevance of further research on the impact of regular yogurt consumption on metabolic processes and disease prevention is discussed.